The effect of incomplete blinking rate on corneal epithelial remodeling after trans-PRK surgery: a six-month study - Yang, Fan; Cheng, Huanmin; Zhao, Shaozhen; Huang, Yue (Frontiers in Medicine, 2024)
To evaluate the impact of incomplete blink rate on corneal epithelial thickness after transepithelial photorefractive keratectomy(Trans-PRK) surgery.Trans-PRK patients were divided into two groups based on preoperative incomplete blinking rates, namely rates ≤ 0.5 (41 right eyes, group A) and rates >0.5 (65 right eyes, group B). We used anterior segment optical coherence tomography to measure the corneal epithelial thickness (CET) and lipiview to measure the number of blinks, incomplete blinking rate, and lipid layer thickness (LLT).In both groups, CET decreased at 1 week and 1 month, and the thicknesses in the IT, T, and ST regions exceeded the preoperative levels. Three months after Trans-PRK, the thickness exceeded the preoperative levels and continued to increase during subsequent follow-ups.The blinking times and LLT in both groups decreased at 1 week and gradually increased but did not return to preoperative levels. Group A maintained an incomplete blinking rate of over 0.5 at all postoperative periods. The incomplete blinking rate of group B remained above 0.5 postoperatively, although there was an improvement compared with preoperative rates. Both groups showed a correlation between changes in CET and incomplete blinking rate. There was a correlation between changes in LLT and the incomplete blinking rate after surgery.Both groups showed uneven corneal epithelia thickening, which became more pronounced approaching the peripheral areas. In addition, changes in CET after surgery were positively correlated with the incomplete blinking rate in both patient groups. There was a negative correlation between postoperative LLT and incomplete blinking rate.